The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5194/bg-15-3717-2018
|View full text |Cite
|
Sign up to set email alerts
|

Variable metabolic responses of Skagerrak invertebrates to low O<sub>2</sub> and high CO<sub>2</sub> scenarios

Abstract: Coastal hypoxia is a problem that is predicted to increase rapidly in the future. At the same time, we are facing rising atmospheric CO 2 concentrations, which are increasing the pCO 2 and acidity of coastal waters. These two drivers are well studied in isolation; however, the coupling of low O 2 and pH is likely to provide a more significant respiratory challenge for slow moving and sessile invertebrates than is currently predicted. The Gullmar Fjord in Sweden is home to a range of habitats, such as sand and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…If we consider our findings in the context of the previously proposed “RI” thresholds, the relationship between Ln RR and theoretical p O 2 / p CO 2 ‐ratio obtained supports criticisms of Seibel and Childress (2012) that the thresholds are inadequate and do not fully capture sources of variation in Ln RR observed in this analysis. Although its use has been challenged (Seibel & Childress, 2012), the only experimental tests thus far available involved marine invertebrates from the Chilean coast, Baltic Sea, and Eastern Australia (Fontanini et al., 2018; Steckbauer et al., 2015; Treible et al, 2018). The responses of marine organisms to RI values within the range of 0.7–1.0, which was proposed to delineate the level at which aerobic respiration must be severely compromised (Brewer & Peltzer, 2009), were modest (Ln RR ≈ −0.4, i.e., 33% reduction in performance compared to controls with RI values of 1.5–1.8, Figure 3a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If we consider our findings in the context of the previously proposed “RI” thresholds, the relationship between Ln RR and theoretical p O 2 / p CO 2 ‐ratio obtained supports criticisms of Seibel and Childress (2012) that the thresholds are inadequate and do not fully capture sources of variation in Ln RR observed in this analysis. Although its use has been challenged (Seibel & Childress, 2012), the only experimental tests thus far available involved marine invertebrates from the Chilean coast, Baltic Sea, and Eastern Australia (Fontanini et al., 2018; Steckbauer et al., 2015; Treible et al, 2018). The responses of marine organisms to RI values within the range of 0.7–1.0, which was proposed to delineate the level at which aerobic respiration must be severely compromised (Brewer & Peltzer, 2009), were modest (Ln RR ≈ −0.4, i.e., 33% reduction in performance compared to controls with RI values of 1.5–1.8, Figure 3a).…”
Section: Discussionmentioning
confidence: 99%
“…A simple linear constraint describing p O 2 and p CO 2 conditions in marine systems may provide a useful metric to understand how the combined extremity of deoxygenation and acidification drives impacts on marine biota. For instance, invertebrates of the Chilean coast and the Baltic Sea experimentally exposed to various p CO 2 and p O 2 combinations exhibited reduced metabolic rates with declining O 2 and rising p CO 2 values (Fontanini, Steckbauer, Dupont, & Duarte, 2018; Steckbauer et al., 2015). However, the reliability of the p O 2 / p CO 2 ‐ratio as a potential indicator of marine taxa responses to CA and CD remains to be tested.…”
Section: Introductionmentioning
confidence: 99%
“…pH conditions registered during the upwelling applied in our study. Apart from single stress responses, Fontanini et al [60] demonstrated that the combination of acidification ( pH 7.6) and hypoxia (2.0-3.5 mg l −1 ) led to a decrease in metabolic rates of A. rubens. Similar negative synergistic effects of acidification and hypoxia were shown for other echinoderms [61].…”
Section: (B) Late Summer Upwelling Events Transiently Decrease Starfi...mentioning
confidence: 99%
“…The heartbeat rate like some other techniques (for example respirometry) is a simplified measure of the metabolic rate of the invertebrate animals (20,21,23,26).The majority of the studies use these experimental techniques under laboratory conditions due to difficulties and complexity of the field measurements. But, in fact, laboratory data usually doesn't reflect the field data (18,20,27). Therefore, researchers followed many processing to keep their experimental animals under conditions nearly approaching that of the field.…”
Section: Discussionmentioning
confidence: 99%